Neuromuscular Training Programs for Injury Reduction in Adolescent Female Running Athletes: A Critically Appraised Topic - Monica Queen; Emily Elgas; Nina German; Alexandra Green; Nicole Rogers; Kellie C. Huxel Bliven (International Journal of Athletic Therapy and Training, 2026)
Introduction : More females are competing at younger ages in running-intensive sports. Given their increased risk for sport-related lower-extremity (LE) injury, it is important to identify effective prevention programs at reducing injury rates in this population. Focused Clinical Question : Are neuromuscular exercise-based programs effective at reducing injury in adolescent females who participate in running-intensive sports compared to a conventional-based program? Summary of Findings : Three randomized controlled studies met the inclusion criteria. Overall, females who performed neuromuscular training had reduced LE injuries, yet two studies with samples extracted from larger data sets were too underpowered to detect differences between groups. Clinical Bottom Line : Limited evidence exists supporting neuromuscular programs to reduce LE injury in adolescent females in running-intensive sports, yet this training has other benefits and few risks. While neuromuscular training is effective in reducing LE injury in other populations (e.g., adult males and females), well-designed studies specifically addressing adolescent females are needed to more conclusively demonstrate neuromuscular training’s impact on injury reduction. Strength of Recommendation : Evidence included to answer this clinical question supports a strength of recommendation grade of B, suggesting limited-quality evidence for neuromuscular programs in adolescent female athletes in running-intensive sports to reduce LE injuries.